Adolescentes usuárias de substâncias psicoativas - Paiva, Elisabete Péres Queiroz de (2010)
This search studied female hospitalized adolescents for treatment of drug addiction in Desafio Jovem Recovery Center of Alcohol and Drug. Aimed to describe the psychodynamics and psychosocial characteristics of adolescents and to identify risk behaviors and health protection of the participants. For data collection, we used the Socio-Demographic Identification and Psychoactive Substances Consumption Questionnaire, the HTP projective test (House-Tree- Person) and the "Screening Inventory of Drug Use (DUSI). Study participants were 14 adolescents in the 12 to 17 years. Most adolescents (78.57%) are children of divorced parents. The first substance used, in the age range of 9 to 14 years, was the cigarette (42.86%), the second was marijuana (35.71%), the third in the 9 to 15 years was alcohol (21.43%), and the fourth substance in the 9 to 16 years was crack (35.71%). The favorite drug of these adolescents is crack (42.9%). The lack of affection is seen as a reflection of one's own life story, with helplessness, with no affection, no trust, isolation, lack of safe social contacts, dissatisfaction with the family environment that is restrictive, showing vulnerability that is present in relation to the pressures experienced in the family environment. The father is often absent in the development of these adolescents. Situations such as neglect, violence and parental abandonment, as well as involvement with licit and illicit drugs by parents and other family members, should be subjected to security measures of public policies to promote family and community health and reduction of harm-related psychoactive substances